Ten Kasina and The Enlightenment Found in Visuddhimagga - Popatlab, Phra Pongsit; Koomkrong, Viroj (Journal of Multidisciplinary in Humanities and Social Sciences, 2022)
The objectives of this article were 1) to study the 10 Kasina found in the Visuddhimagga text and 2) to analyze the 10 Kasina for enlightenment found in Visuddhimagga. The studied data was collected from primary sources of Early Buddhism and other concerned papers, then brought for analysis and finally compiled in descriptive type. The findings revealed an analysis of Kasina for enlightenment found in Visuddhimagga revealed that for Paṭhavīkasiṇa practice, for example, an object of tranquility’s meditation, prior to Vipassana, meditator contemplates at a round mud with 1.4 inches which requires entirely observing as one, not only a participatory object. The perceptual figure of Kasina, an object imagined lying on earth perception was called as Paṭhavikasiṇa. Then having completed 4 form absorptions, and 4 formless absorptions through Paṭhavīkasina concentration, meditator can use it as a base for the Vipassana entrance called as Samathayānika which refers to the mental development by tranquility before insight investigation. This Samathayānika is a mental training for liberation according to Cetovimutti or mentality liberation type, which leads to Arahatship as Ubhatobhāgavimutti etc.